Comparative Analysis of the Usage Expressions of COVID-19 Prevention Signs in Japanese and Indonesian: A Case Study of Modern Shopping Mall - Afifah, Muthi; Sugihartono (Universitas Negeri Semarang, 2024)
This study aims to analyse the expressions used on prohibition signs containing preventive measures against the spread of COVID-19 in Japan and Indonesia. Data were collected from modern shopping centres in Tokyo, Osaka, Jakarta, and Surabaya during the COVID-19 pandemic in 2021-2022. The expressions on COVID-19 prohibition signs are categorised based on the presence or absence of polite forms and the use of implicit or explicit sentence structures. Therefore, this research analyses the types of expressions used and aims to determine whether there are similarities and differences between Japan and Indonesia. The result of this study found that there has a tendency to use implicit sentences rather than explicit ones on COVID-19 prohibition signs in Indonesia and Japan. However, there is a difference in the use of polite forms. Japan tends to use polite forms, while Indonesia tends to use non-polite forms.